Pregnancy and its role in breast cancer - Martins, Filipe (2008)
Abstract Early full-term pregnancy is the only recognized factor able to prevent breast cancer. There are several hypotheses to explain the mechanisms of this protection, namely an altered hormonal milieu, a differentiation process or a switch in stem cell properties. To explore them, authors have been using animal models, mainly in rodents. Hormonal administration with estrogen and progesterone was the most widely used process to mimic the mammary changes during pregnancy. We have recently proposed that this enigmatic protective role of a full-term birth in breast cancer is carried out by tumor inhibition mediated by differentiated mammary epithelial cells. This explanation may give a new perspective of breast cancer prevention and treatment.